Population Income and Poverty in Lithuania - Šileika, Algis; Blažienė, Inga (Ekonomika, 2000)
The discussion between defenders of two different concepts of poverty – absolute and relative -are still going on in Lithuania. The authors of the Lithuanian poverty alleviation strategy project arc offering to use only the relative poverty line in evaluating poverty in Lithuania. The authors of the paper represent the opinion that it is too early to refuse the concept of absolute poverty in Lithuania these days. Relative poverty concept becomes urgent only after the relative poverty line increase enough to exceed the absolute poverty line. The situation in Lithuania these days is reversed: the level of average population income and expenditure is low and relative poverty line, calculated as a percentage of this average is far below poverty line calculated when taking into account the nutritional standards of consumption. Authors arc analysing different concepts of poverty in the paper: the concepts of social and physiological poverty and the absolute and relative poverty lines. They offer to use minimal normative consumption budget (MNCB) as a basis fur calculating absolute social poverty line and present (he main principles of constructing such a budget. The MNCB wa. modelled a, an aggregated measure of minimal subsistence level by scientists from the National Nutrition Centre of Lithuania and the Lithuanian Institute of Labour and Social Research. The MNCB defines a minimal level of satisfying the indispensable physical, spiritual. intellectual and social needs that, to the opinion of the society, ensures minimal reproduction conditions for one person undertaking the job that is not harder and more difficult than the average one. In estimating the budgets objective minimal consumption norms as well as actual consumption, and especially nutrition, habits of Lithuanian population, prevailing traditions, peculiarities and the current economic development level in the country were taken into account. Using this measure the distribution of population income in Lithuania is analysed according to the residence place, socio-economic group and the composition of the household.